(untitled) (Bulletin KNOB, 1989)
Living and working at Amsterdam Johannes Schouten (1716-1792) became in 1744 member of the guild of gold and silversmiths and in 1756 of the guild of booksellers. He was only amateurishly occupied with the execution of topographical and townscape-drawings. His son Hermanus Petrus Schouten (1747-1822) lived in Haarlem from 1792 on but still made regularly drawings of his native town, besides rendering strange town- and landscapes during his journeys, which prints unfortunately seldom are dated. The modest amount of signed townscapes of Amsterdam and environment by Johannes Schouten are sketched with black crayon and, opposed to the pen-strokes of his son, outlines and details are rendered with pencil. Showing stylistic features of the drawings of father and son the attribution of the unsigned sheets is problematic, Schouten often making copies after contemporaries and the son often finishing what his father had started. Taught by Paul van Liender (1731-1797), a pupil of Cornelis Pronk (1691-1759), H.P. Schouten perfectly mastered the rendering of chiaroscuro after Pronk. The three categories within his oeuvre as there are the engravings for the Atlas van Pierre Fouquet, the pen-drawings in Indian ink with grey washing and the third category, executed in colour, supply a detailed image of his working-method. The first and third category being preceded by a sketch registering the topographical situation forms the second category a quite puzzling comparison between the works of father and son. Figures were added to the preliminary sketches for the Atlas van Fouquet. Although these engravings are seldom signed, comparison between prints and preliminary sketches undoubtedly points out Schouten as their maker. His colourful detailed pen drawings of the third category depicting bourgeois life at the end of the 18th century, already at the time were a real collector’s item. Schouten’s almost photographic prints often are less realistic than it seems by the omission of architectural details to obtain a better composition. While fictious trees and figures are used for this same purpose, strengthened perspective and chiaroscuro are even more surprising employed to manipulate reality. Part of Schouten’s preliminary sketches and other sheets were owned and accurately copied by Gerrit Lamberts (1776-1850) and, although less capable, by Schouten’s pupil G.D. Galen (1755-1794). The study of Schouten’s and of 18th century topographic prints in general learns, that the measure of reality of these drawings only can be determined by analyzing several pictures of the same subject at the same time. Hardly any stylistic development present in his work, the many unsigned sheets and the often large time difference between preliminary sketch and definitive version still evoke many questions as to the dating of H.P Schouten’s work.